Glycyrrhizin inactivates toll‐like receptor (TLR) signaling pathway to reduce lipopolysaccharide‐induced acute lung injury by inhibiting TLR2. Issue 4 (10th September 2018) - Kong, Delei; Wang, Zanfeng; Tian, Jie; Liu, Tingwei; Zhou, Hui
Abstract: Objective: This study aimed to explore glycyrrhizin on acute lung injury (ALI) and how glycyrrhizin (GL) attenuated lipopolysaccharide (LPS)‐induced ALI. Methods: Bioinformatics analysis was performed to screen the expressed genes in LPS‐induced ALI mice. The enrichment of functions and signaling pathways of deregulated genes were conducted. Combined with DIGSEE and STICH, the target gene for further investigation was chosen. To verify target gene in mice, we performed experiment in vivo. Forty mice were randomized into NC, LPS, LPS + S, and LPS + GL group. Mice in the LPS + GL group received glycyrrhizin l mg and mice in LPS + S received saline. Then, HE and Masson staining detected pathological changes of lung tissues; enzyme‐linked immunosorbent assay analyzed bronchoalveolar lavage fluid concentrations of MIP‐2, mice growth‐related oncogene homologue (KC), IL‐4, IL‐6, GM‐CSF, IFN‐γ, and IgM; western blot analysis determined the expression of toll‐like receptor (TLR) signaling and NF‐κB pathway‐related proteins. Results: Tlr2 which was not only upregulated but also closely related to glycyrrhizin. TLR2 was upregulated in following LPS induced in cells and TLR2 overexpression‐activated TLR signaling pathway to promote ALI. After glycyrrhizin treatment, the expression of TLR2 was reduced. Furthermore, it was found out that the number of inflammatory cells, collagen deposition, MIP‐2, KC, IL‐4, IL‐6, GM‐CSF, and IFN‐γ expression increased in ALI mice and glycyrrhizin mitigated it. Similarly, the expression of TLR signaling pathway and NF‐κB pathway‐related protein also increased. Conclusion: Glycyrrhizin functioned as a suppressor in TLR signaling pathway to reduce LPS‐induced ALI by inhibiting TLR2. Abstract : 1. Glycyrrhizin could mitigate the severity of LPS‐induced ALI by inhibiting proteins in TLR signaling pathway and NF‐κB signaling pathway. 2. Glycyrrhizin inactivated toll‐like receptor signaling pathway to reduce acute lung injury incurred by lipopolysaccharide through suppressing TLR2.